The Relationship between Sport Orientation and Sport Anxiety in Athletes Participating in 10th Student Sport Olympiad - Akbar Jamshidi; Elahe Arab Ameri; Narjes Alizadeh; Afshin Salmaniyan (University of Tehran, 2012)
The aim of this study was to investigate the relationship between sport orientation and competitive anxiety in male and female athletes of team and individual sports who participated in 10th student sport Olympiad (1389). The present study was descriptive and correlation method was used. For this purpose, 688 subjects (337 females and 351 males) were selected as the sample by simple random sampling method. All subjects in the sport camp filled out Gill sport orientation and a few hours before the competition, they filled out Martin's competitive anxiety questionnaire. The collected data were analyzed by multivariate regression analysis, multivariate analysis of variance (ANOVA) and independent t test. The results showed that sport orientation could predict competitive anxiety. In fact, when competitiveness and goal orientation increased, competitive anxiety reduced while when win orientation increased, competitive anxiety increased as well. Female athletes were more anxious than males (P=0.001). Those subjects who were a member of individual sports had more competitive anxiety than team sports (P=0.004). Male athletes were more competitive and win oriented than female athletes while female athletes were more goal oriented than male athletes (P=0.002). However, there was no significant difference in sport orientation between team and individual sports (P>0.05).